(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
Abbatoirs have to produce meat that complied requisite of safety, healthy, wholeness and halal. Animal origin product have to requisite basic safety product which implementated of hygine sanitation as production processed. The research aim was to evaluate implementation of hygine sanitation system on 1st categrory abbatoir at Bogor Regency to complied safety and quality assurance of product. Observations on the implementation of hygienic sanitation were carried out using an evaluation matrix of the suitability of physical requirements with the criterion parameter assessment method based on the Regulation of the Minister of Agriculture Number 13/2010. The best suitability value (NK) of 3 was obtained on the environmental hygiene indicator and the absence of the use of chemicals, while the other sanitation hygiene indicators were worth 2 (less appropriate). The results of testing on meat for the content of Salmonella sp. is negative and the Total Plate Count test is between 7.1 x 103 - 5.2 x 104 cfu/g below the SNI threshold (1.0 x 106 cfu/g). The test for E. coli in meat was above the threshold of suspected contamination from the water used. Validation of hygiene sanitation practices was carried out by means of Colliform swabs on knives, palms hand and clothing of officers. Colliform swab test of the officer’s palm hand, which is 5.4 x 102 cfu/g, shows a value above the allowable threshold. The results of the evaluation of the application of sanitation and hygiene in the abattoir are quite good but still need improvement. Priority improvements are the equipment of cleaning facilities, water quality testing and improvement of personal hygiene understanding.